EKSISTENSI KOMUNIKASI TERHADAP UPAYA PEMULIHAN SOSIAL EKONOMI PASCA BENCANA DI KABUPATEN LUWU UTARA - Muhammad Taufik Rahmansyah; Hafied Cangara; Arianto Arianto (Jurnal Dakwah Tabligh, 2021)
Communication has always been a medium for every human being to coordinate or interact socially, whether in the face of a disaster or not. It becomes normal when communication is needed in post-disaster recovery efforts. Although communication is not able to completely change the overall socio-economic aspects, it is not surprising that communication cannot be separated in every disaster management. Because, communication can present an organized handling system. The purpose of this research is to examine the extent to which communication plays its role and function in rehabilitation (recovery) efforts after the extraordinary fury of banjir bandang natural disasters. Where the incidence of natural disasters that hit North Luwu Regency caused a lot of losses, especially from the socio-economic aspects (education, housing, health, religious activities, facilities and infrastructure, trade, umkm, and also agriculture). This is because many people have experienced a downturn, even parts of Masamba and Baebunta sub-districts also feel the impact. In this research the researcher applied a descriptive qualitative research method using a case study approach. Where in determining the data source, the writer uses purposive sampling. The results of this study are that in this recovery effort there is a joint responsibility (North Luwu Regency government)